Mannose-binding lectin 2 gene polymorphism and susceptibility to upper respiratory tract infection among endurance athletes - Zehsaz, F.; Farhangi, N.; Legge, M. (European Journal of Sport Science, 2014)
The aim of this study was to investigate the influence of mannose-binding lectin 2 (MBL2)-exon-1 gene polymorphisms on upper respiratory tract infection (URTI) incidence among endurance athletes. To this end, 100 healthy elite male athletes participating in the study were classified as either healthy or prone to frequent URTI. Blood samples, DNA isolation, multiplex polymerase chain reaction (PCR) and conventional PCR-RFLP were performed. Genomic DNA was extracted from peripheral leukocytes of whole blood samples using the QIAmp DNA Blood Mini Kit. For comparison of the distribution of genotypes between two groups and for estimating odds ratios (OR) for URTI susceptibility in relation to the MBL2-exon-1 polymorphism, Pearson's chi-square and logistic regression method were used, respectively. The MBL2-exon-1 genotype distribution differed between athletes with URTI and healthy athletes (Chi2 = 7.81, p = 0.02). The AO and AO + OO genotypes of MBL2 were observed at a greater frequency in the illness-prone group compared with the healthy group (34.04% vs. 11.32%). In conclusion, findings from this study have identified a potential role of genetic variation in influencing the risk for URTI in athletic populations and single-nucleotide polymorphisms (SNPs) in the MBL2-exon-1 genes were associated with an altered risk profile. These measures may have a predictive value in the identification of individuals who are more likely to experience recurrent infections when exposed to high physical stress in the areas of athletic endeavour.